Digital Citizenship Education as a Pathway to SDG Alignment (4, 10, and 16): A Qualitative Study of Indonesian Elementary Education - Damanik, Prince Clinton Immanuel Christian; Lie, Catherine (CV Berkah Syahdin Trust, 2025)
This study explores the implementation of digital citizenship education in Indonesian elementary schools as a pathway to achieving the Sustainable Development Goals (SDGs) 4 (Quality Education), 10 (Reduced Inequalities), and 16 (Peace, Justice, and Strong Institutions). Using a qualitative descriptive design and thematic analysis, the research examines national policies, academic literature, and school-based initiatives related to the Kurikulum Merdeka, Profil Pelajar Pancasila, and Adiwiyata (Green School) programs. Findings reveal that digital citizenship education is increasingly integrated through projects, digital storytelling, and ethical online engagement that nurture students’ critical thinking and civic responsibility. However, challenges such as limited teacher competence, uneven digital infrastructure, and the absence of localized ethical frameworks persist. The study’s theoretical contribution lies in integrating Pancasila ethics with digital citizenship and sustainability education, framing moral, civic, and technological dimensions as mutually reinforcing components of transformative learning. This synthesis underscores the importance of coherent policy implementation, teacher professional development, and culturally grounded pedagogy to promote equitable, ethical, and sustainable digital learning environments aligned with the SDGs.